KINETICS STUDY ON NITRATION OF METHYL RICINOLEATE - Abdullah Abdullah; Triyono Triyono; Wega Trisunaryanti; Winarto Haryadi (Universitas Gadjah Mada, 2012)
Kinetics parameter values of methyl ricinoleate nitration (rate constant, reaction order and the rate of reaction) have been determined. Nitration was carried out with both concentrations of HNO3 and acetic anhydride in excess to the concentration of methyl ricinoleate. Thus, the kinetics parameter value was only affected by the concentration of methyl ricinoleate. Based on kinetic study conducted, it could be concluded that the nitration follows pseudo first-order, and the reaction rate for methyl ricinoleate with initial concentration of 0.375, 0.325 and 0.250 M were 3.736 x 10-5, 2.471 x 10-5, and 1.724 x 10-5 M/s respectively, with the rate constant at 28 °C was 6.667 x 10-4 (s-1). Based on evaluation of FTIR spectra could be estimated that the nitration produces compounds containing functional groups of -NO3 and -NO2.